Rule of Islamic Law dan Mekanisme Penambahan Kewenangan Constitutional Complaint Mahkamah Konstitusi - Anggar Putra (Bulletin of Community Engagement, 2024)
The Constitutional Court is the guardian of the constitution, the final interpreter of the constitution, the protector of human rights, the protector of the citizen's constitutional rights), protector of democracy (the protector of democracy). These five authorities place the Constitutional Court as the sole guardian of citizens' constitutional rights which are comprehensively explained in the law. The Constitutional Court as the enforcer of "constitutional supremacy" and the interpretation that the Constitution does not only contain basic norms, but actually within the body of these norms there are principles and morality which are the main pillars of creating the ideals of a state that upholds the law. Although in reality the Constitutional Court has not been able to accommodate all the aspirations of the people universally. However, with the expansion of the Constitutional Court's authority to examine Constitutional Complaints, it is an extraordinary legal effort in fighting for and defending constitutional rights. This research is normative-Juridical research, with a statute approach and Islamic nomocracy. The data source used is library research. The results in this study, there is a mechanism for adding a constitutional complaint by amending the 1945 Constitution of the Republic of Indonesia, amending Article 29 paragraph (1) UU/48/2009, and amending Article 10 UU/24/2003. The findings in this study, there are opportunities and mechanisms for adding constitutional complaint authority by carrying out Legislative Interpretation efforts.